Carotid Blowout Management in the Endovascular Era: A Single Institution Series. (16th November 2020) - Weinberg, Joshua; Sweid, Ahmad; Joffe, Daniel; Piper, Keenan; Abbas, Rawad; Hussain, Zubin; Anderson, Brigitte; Gooch, M. Reid; Herial, Nabeel; Tjoumakaris, Stavropoula I; Hasan, David M; Zarzour, Hekmat; et al.
Abstract: INTRODUCTION: Carotid blowout syndrome (CBS) is a potential complication of head and neck cancer (HNC) and its therapy associated with high morbidity and mortality. Recent advances in endovascular techniques have improved patient outcomes. METHODS: We conducted a retrospective analysis and identified 34 consecutive patients that underwent 38 endovascular procedures for CBS from 2008–2019 at our institution. Data collection was performed on patient demographics, type of cancer, previous cancer treatments, type of CBS, location of bleed, diagnostic work-up, endovascular treatment, and procedural outcomes and complications. RESULTS: 34 consecutive patients with a mean age of 58.6 years ± 13.2 underwent 38 endovascular procedures for CBS from 2008 through 2019. Technical success was achieved in 100% of endovascular procedures. Major complications occurred in 3 (7.9%) procedures including stroke in 2 (5.3%) procedures and rehemorrhage in 1 (2.6%) procedure. Minor complications occurred in 10 (26.3%) procedures including stroke in 1 (2.6%) procedure, rehemorrhage in 4 (10.5%) procedure, infection in 1 (2.6%) procedure, and other complications occurred in a total of 4 (10.5%) procedures. Overall in-hospital mortality occurred in 2 (5.9%) patients, and 25 (73.5%) patients were alive at latest follow-up at a mean of 10.7 months ± 14.0. CONCLUSION: The endovascular treatment of CBS is safe and effective with relatively low rates of morbidity and mortality compared to other currently available treatment modalities. However, the overall rate of complications demands attention and sheds light on the need for further improvement in management.